Minimum tillage on vertisols lowland increases rice production and soil properties - Fitria Zulhaedar; Makruf Nurudin; Eko Hanudin (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2023)
Current land management is a challenge for wetlands vertisol soil types, especially on the rice production, which often clashes with future soil quality. This study aimed to obtain optimal performance of rice growth and physical and chemical properties of vertisol soil on various tillage systems. The study was carried out in the vertisol rice fields of Batu Bolong sub-village, Ungga village, Southwest Praya District, Central Lombok Regency, West Nusa Tenggara during the second growing season (March-October) in 2021. The experimental design was arranged in a Completely Randomized Design consisting of three levels of: no-tillage as T1, minimum tillage as T2, and maximum tillage as T3, with each treatment being repeated five times. The use of production inputs and infrastructure was uniform in all experimental plots. The results showed that T2 treatment had some of the best parameters for rice growth and yield as well as the physical and chemical properties of the land. Plant height and number of tillers at T2 were significantly more maximal in observing the vegetative phase. The dry weight of 1000 grains and rice productivity from the highest were respectively T2 > T1 > T3. The physical and chemical parameters of the soil also showed the same order. Thus, it can be said that minimum tillage is the best tillage system to obtain the growth and yield of rice in the second growing season and the most optimal physical and chemical properties of vertisol soil.